Customer's assessment towards food and service quality of kiss the ice liquid nitrogen ice cream - Cusipag, Jodie Ann A. (Manila : National University, 2017)
This study is significant as its result will provide empirical data on the over-all experience of customers towards Kiss the Ice Liquid Nitrogen Ice Cream.
Approval Sheet -- Certificate of Originality -- Acknowledgement Sheet -- Abstract -- Table of Contents -- List of Tables -- List pf Figures -- Chapter 1. The Problem and its Background -- Chapter 2. Literature Review -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation of Data -- Chapter 5. Summary, Conclusions and Recommendations.
Includes bibliographical references.